2015
DOI: 10.1146/annurev-immunol-032414-112334
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Antigen Receptor Recognition of Antigen-Presenting Molecules

Abstract: The Major Histocompatibility Complex (MHC) locus encodes classical MHC class I and MHC class II molecules and nonclassical MHC-I molecules. The architecture of these molecules is ideally suited to capture and present an array of peptide antigens (Ags). In addition, the CD1 family members and MR1 are MHC class I-like molecules that bind lipid-based Ags and vitamin B precursors, respectively. These Ag-bound molecules are subsequently recognized by T cell antigen receptors (TCRs) expressed on the surface of T lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
703
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 660 publications
(734 citation statements)
references
References 151 publications
(214 reference statements)
29
703
0
2
Order By: Relevance
“…Indeed, recent studies in several systems have demonstrated that ligand binding can alter protein flexibility at distant sites, resulting in long range transmission of biological signals, even in the absence of crystallographically observed structural changes (47)(48)(49)(50). This process, known as dynamic allostery, is of special interest in cases such as the TCR, where x-ray crystallographic studies of multiple TCRs in free form and bound to pMHC have so far failed to identify clear and consistent conformational changes in the TCR C␣ or C␤ domains that could be unambiguously attributed to antigen binding (4,8,10). Future studies will examine the possibility that MBP-HLA-DR4 ligation by MS2-3C8 induces allosteric changes in TCR dynamics that are transmitted to the CD3 signaling apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies in several systems have demonstrated that ligand binding can alter protein flexibility at distant sites, resulting in long range transmission of biological signals, even in the absence of crystallographically observed structural changes (47)(48)(49)(50). This process, known as dynamic allostery, is of special interest in cases such as the TCR, where x-ray crystallographic studies of multiple TCRs in free form and bound to pMHC have so far failed to identify clear and consistent conformational changes in the TCR C␣ or C␤ domains that could be unambiguously attributed to antigen binding (4,8,10). Future studies will examine the possibility that MBP-HLA-DR4 ligation by MS2-3C8 induces allosteric changes in TCR dynamics that are transmitted to the CD3 signaling apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Affinities of this magnitude are typically associated with TCRs that recognize nonself/microbial epitopes (25,26). We previously observed how HLA-DQ8-glia-a1 recognition by a TRAV26-2/TRBV9 TCR and HLA-DQ2-glia-a2 recognition by three TRAV26-1/TRBV7-2 TCRs depended on a CDR3-encoded Arg (9,10).…”
Section: ) This Trbv9mentioning
confidence: 98%
“…T he T-cell receptor (TCR) expressed on T lymphocytes of the adaptive immune system is a stout and squat (12-nm wide × 8-nm tall) multisubunit surface complex with a ligand binding moiety that is an αβ disulfide-linked heterodimer buttressed by the associated invariant CD3 subunits (1)(2)(3). The αβ chains are each encoded by V and J gene segments and in the case of the β, a D segment as well (4).…”
mentioning
confidence: 99%